2011
DOI: 10.1068/p6776
|View full text |Cite
|
Sign up to set email alerts
|

Footprints Sticking Out of the Sand. Part 2: Children's Bayesian Priors for Shape and Lighting Direction

Abstract: The shading information in images that depict surfaces of 3D objects cannot be perceived correctly unless the direction of the illuminating light source is known, and, in the absence of this knowledge, perception in adults is consistent with a light-from-above Bayesian prior assumption. In order to investigate if children make use of a similar assumption, 171 children between the ages of 4.6 and 10.8 years were tested using 20 images containing shading information, where the shape depicted in each image can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
2
20
3
Order By: Relevance
“…Our findings are in contrast to other research reporting developmental increases in responses consistent with light-from-above prior (Stone, 2011, Stone and Pascalis, 2010, Thomas et al, 2010), although the evidence is not clear-cut. Thomas et al (2010) found an overall effect of age on children’s interpretation of ambiguous stimuli, so that trials answered assuming light from above increased across childhood.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to other research reporting developmental increases in responses consistent with light-from-above prior (Stone, 2011, Stone and Pascalis, 2010, Thomas et al, 2010), although the evidence is not clear-cut. Thomas et al (2010) found an overall effect of age on children’s interpretation of ambiguous stimuli, so that trials answered assuming light from above increased across childhood.…”
Section: Discussioncontrasting
confidence: 99%
“…The results reported here provide further evidence that the perception of shape from shading, like other aspects of visual perception (Purves, Wojtach & Lotto, 2011), arises from interactions with the natural world rather than internal biases that give rise to illusory perception (Stone, 2011; Stone & Pascalis, 2010). Importantly the demonstration here does not depend on a complex analysis of psychophysical data, but rather a simple shape-from-shading drawing and a candle would do, allowing even Rittenhouse (1786) to experience this himself.…”
Section: Discussionsupporting
confidence: 57%
“…Contrary to those who theorized that the overhead bias is hard-wired and innate (Ramachandran, 1988; Hoffman, 1998), Stone found that the overhead Bayesian prior requires developmental experience (Stone, 2011). A recent study demonstrated that the assumption that light comes from above has a lesser role than lighting cues in the perception of shape from shading (Morgenstern, Murray & Harris, 2011).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…There may also be agerelated changes in the effects of grouping on speed discrimination. Although children make use of prior information from an early age (Sciutti, Burr, Saracco, Sandini, & Gori, 2014;Thomas, Nardini, & Mareschal, 2010), the weighting assigned to these priors may change as the child develops (Stone, 2011;. Furthermore, it has been suggested that the extent of global processing increases with age (Dukette & Stiles, 1996;Harrison & Stiles, 2009;Kramer, Ellenberg, Leonard, & Share, 1996;Poirel, Mellet, Houdé, & Pineau, 2008;Tada & Stiles, 1996;Vinter, Puspitawati, & Witt, 2010; but see also Enns & Girgus, 1985).…”
Section: Introductionmentioning
confidence: 99%